English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

9(x-3)^2-5=0
solve in square roots

2007-03-04 16:14:24 · 4 answers · asked by yep yep yep 3 in Science & Mathematics Mathematics

4 answers

9(x - 3)^2 - 5 = 0

9(x - 3)^2 = 5

(x - 3)^2 = 5/9

x - 3 = +/- sqrt(5)/3

x = 3 +/- sqrt(5)/3

2007-03-04 16:18:33 · answer #1 · answered by Puggy 7 · 0 0

this is one way:
9(x-3)^2 - 5 = 0
9(x-3)^2 = 5
(add 5 to both sides)
(x-3)^2 = 5/9
(divide both sides by 9)
x-3 = + or - the square root of 5/9
(because (x-3)^2 is = to 5/9, the square root of 5/9 therefore must = (x-3). Due to the fact that x could be positive or negative we must say that the square root of 5/9 can be + or -)
x = (+ or - the suare root of 5/9) +3
(add 3 to both sides)

hope u can make sense of that

2007-03-05 00:35:09 · answer #2 · answered by popcorn 2 · 0 0

first 9(x - 3)^2 - 5 = 0
bring five over
9(x - 3)^2 = 5
divide by nine
(x - 3)^2 = 5/9
then square root it
x - 3 = +/- sqrt(5)/3
and add 3
x = 3 +/- sqrt(5)/3

2007-03-05 00:25:21 · answer #3 · answered by loktao s 2 · 0 0

9(x-3)^2=5

(x-3)^2=5/9

x-3= plus minus sqroot(5/9)
x= plus minus sqroot(5/9)+3

2007-03-05 00:19:20 · answer #4 · answered by infinitesnowboy 2 · 0 0

fedest.com, questions and answers